Effects of age and breed on trace elements content in cattle muscle and edible offal - Hayrunnisa, ÖZLÜ; ATASEVER, Mustafa (Asian Journal of Medical and Biological Research, 2018)
In this study, effects of age and breed on the trace elements content in different muscles (M. longissimus dorsi, M. longissimus thoracis, M. psoas major, M. intercostalis internus, M. semispinalis capitis, M. biceps femoris, M. biceps brachii) and edible offal (liver, kidney, heart) of cattle were investigated. Iron (Fe), zinc (Zn), copper (Cu), lead (Pb) and cadmium (Cd)contents of muscles and edible offal were determined by inductively coupled plasma-optic emission spectrometry (ICP-OES).According to the results obtained in this study, the content of Cu in M. longissimus dorsi of Eastern Anatolian Red (EAR) breed cattle was higher than Brown Swiss (BS) breed cattle, and the content of Cu in M. longissimus dorsi was statistically significant among the breeds (p<0.05). On the other hand, the highest Cu content in kidney and the highest Cd content in liver were observed the 4-year-old cattle, and the content of Cu in kidney and the content of Cd in the liver were statistically significant among the ages (p <0,05). Besides, the highest contents of Fe, Cu and Cd were found in the edible offal of EAR breed cattle aged 4 years. The mean values of the trace elements found in cattle muscles were ranked as Zn>Cu>Fe>Pb>Cd, whereas the mean values of the trace elements found in edible offal of cattle were ranked as Cu>Fe>Zn>Pb>Cd. Our results suggest that trace element content may vary in both muscles and offal depend on the breed and age of the cattle. Asian J. Med. Biol. Res. June 2018, 4(2): 157-163